2015
DOI: 10.1039/c5ra05209b
|View full text |Cite
|
Sign up to set email alerts
|

HOTf-catalyzed intermolecular hydroamination reactions of alkenes and alkynes with anilines

Abstract: Herein, the intermolecular hydroamination of alkenes and alkynes with anilines catalyzed by HOTf under mild conditions has been developed.This reaction provides one of the simplest alkene and alkyne addition methods and is an alternative to metal-catalyzed reactions. At the same time, the intramolecular hydroamination of alkynes with anilines proceeds smoothly to obtain quinolines. We found that this strategy is efficient in building complex structures from simple starting materials in an environmentally benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Michael addition is one of the simplest and most effective strategies to prepare β-amino acid esters. Recently, Ahmed has reported the Michael addition of aromatic amines mediated by KOtBu [10]; HOTf (trifluoromethylsulfonic acid) was also used to catalyze the Michael addition of aromatic amines, and good yields were obtained within 4 h [11]. However, the use of acids and alkalis has brought challenges to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Michael addition is one of the simplest and most effective strategies to prepare β-amino acid esters. Recently, Ahmed has reported the Michael addition of aromatic amines mediated by KOtBu [10]; HOTf (trifluoromethylsulfonic acid) was also used to catalyze the Michael addition of aromatic amines, and good yields were obtained within 4 h [11]. However, the use of acids and alkalis has brought challenges to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, hydroaminations and hydroarylations are among the most sought-after reactions because of their high atom economy. In particular, we were interested in the intermolecular addition of anilines to olefins (Scheme ). Common approaches for this reaction include the use of ligand-modulated late transition metals, strong Brønsted acids, and earth-abundant metals. There are some reports on the use of ionic liquids in this type of reaction, especially for the reaction of the more reactive acetylenes and activated olefins or for reactions (co)­catalyzed by Brønsted acids. …”
mentioning
confidence: 99%
“…We further conducted the Cu­(OTf)-catalyzed reaction at a lower temperature (40 °C) by increasing the amount of Cu­(OTf) to 10 mol % in dioxane or THF and succeeded in obtaining the product 4aa without any reduced yield (entries 14 and 15). Unfortunately, the reaction at room temperature resulted in a lower yield (78%) (entry 16), and this result indicated that the reaction requires 40 °C to provide quantitative yields in 12 h. To avoid the possibility that TfOH, which might be produced from Cu­(OTf) in situ, catalyzed the hydroamination reaction, we carried out the reaction of 1a with 2a in the presence of a catalytic amount of TfOH (1 or 10 mol %) and confirmed that not even a trace amount of the product was formed (entry 17). Furthermore, we examined the Cu­(OTf) 2 -catalyzed reaction in other solvents, such as CH 3 CN or toluene, and concluded that THF is the best solvent for this hydroamination reaction (entries 18 and 19).…”
mentioning
confidence: 99%